Spoiler alert! : the badass book of movie plots - Espinoza, Steven; Fernandez, Kathleen Killian; Kaay, Chris Vander (London, United Kingdom : Laurence King Publishing, 2020)
Celebrate Hollywood film-making in all its formulaic and predictable glory. Spoiler Alert! takes 38 mainstream movie genres, from 'Teen Sex Comedy' and 'Buddy Action Comedy' to 'Film Noir Detective Thriller' and 'Alien Invasion Thriller', and through detailed illustrations reveals what makes them so hilariously recognizable - the plots, the key lines of dialogue, the essential visuals, the crucial characters and even the indispensable props
Keywords: Motion pictures -- Plots, themes, etc